Resultado de enfermagem comportamento de prevenção de quedas : validação de indicadores - Costa, Alice Gabrielle de Sousa (2014)
This study aimed to validate the nursing outcome Fall prevention behavior from the Nursing Outcomes Classification (NOC). The validation process focused on people with stroke and their caregivers in the home context. This is a methodological study performed in two stages (content and clinical validation) by a tool proposed by Vitor (2010) who presented 28 indicators and operational definitions related to the general population. The tool was revised and organized in 22 indicators towards to the home environment which is the most common place where falls from height happen. The content validity stage was started with assessment by judges about the appearance. Then, 22 specialists evaluated the titles and definitions of each indicator according to psychometric criteria of simplicity, clearness, precision and suitability. After perform the changes suggested by the specialists, the clinical validation was performed at first by a pilot test in order to adjust the tool to the population. This stage was developed with 106 patients and/or caregivers interviewed by two pairs of trained professionals in the ambulatory service of two hospitals that are reference in the care of people with stroke. One pair of evaluators applied the form with the operational definitions while the other pair applied the form with only the titles and NOC scale. The data were organized in sheets and analyzed by the SPSS 22 program through the calculation of the binomial test. The clinical validation stage applied the Friedman test to verify differences among the evaluators, the calculation of the minimum significant difference (MSD), Cronbach alpha and intraclass correlation coefficient (ICC) to compare the evaluators’ assessment. The study was approved by an Ethical Committee by the nº49.912 and nº392.531; all the participants (specialists, patients and caregivers) were oriented about the goals and the Consent Term. At the content stage, the specialists were most female, with age average of 33.1 years old, 9.5 years of graduation, PhD, working in Post-secondary Institutions. The indicators statistically significant by the Binomial test were: Attaches small rugs and Controls restlessness and all of them were appropriated to the patient with stroke (100% and p=1.000). Most participants were male (51.9%), elderly people, married, retired, with low school grade and low income, living with family and with physical sequelae from the stroke, which requires the need of a caregiver. The Friedman test showed differences in the evaluations of the pairs of professionals for twelve indicators (p<0.05), five of them showed difference in the mean rank higher than the MSD. All the indicators showed statistical significance (p<0.001) and the ICC. This stage was important to realize the need of keeping or not the indicators, which were 18 at the end. Thus, it is noted that the tests showed more agreement between de pair that used the tool with the indicators for each definition. It is possible to highlight the efficiency of empirical references construction and its suitability to specific populations, besides the need of continuous researches in this field of study.